Upregulation of Ets1 expression by NFATc2 and NFKB1/RELA promotes breast cancer cell invasiveness. (November 2018) - Kim, Gi-Cheon; Kwon, Ho-Keun; Lee, Choong-Gu; Verma, Ravi; Rudra, Dipayan; Kim, Taemook; Kang, Keunsoo; Nam, Jong; Kim, Young; Im, Sin-Hyeog
Abstract Breast cancer is highly aggressive and is the leading cause of cancer-related mortality in women in developed countries. The ETS proto-oncogene 1 (Ets1) has versatile roles during the cellular processes of cancer development. It is often highly expressed in breast cancers and mediates migration and invasion of human breast cancer cells. However, underlying mechanisms ofEts1 gene expression is still ambiguous. Here, we identified a core-regulatory element (CRE) located in the Ets1 promoter region (−540/−80 bp from TSS) that contains elements responsible for associating with NFATs and NF-κBs. Compared with the less metastatic breast cancer cells, metastatic breast cancer cells (MDA-MB-231) show open chromatin configurations in the CRE, which facilitates direct binding of NFATc2 and/or NFKB1/RELA complex to trans-activateEts1 transcription. Moreover, enhanced level ofNfatc2 andNfkb1 positively correlated with Ets1 expression in the human breast cancer specimens. Deletion of the CRE region by CRISPR/Cas9 system resulted in significant reduction in Ets1 expression, which led to alterations of Ets1-mediated transcription programs including tumor invasiveness-related genes. Proper regulation ofEts1 gene expression by targeting the NFATc2 and NFKB1/RELA interaction could be a potential therapeutic target for Ets1-mediated metastatic breast cancer.